AN INTEGRATIVE AND COLLABORATIVE APPROACH TO ASSOCIATING ADVERSE BIRTH OUTCOMES AND INDUSTRIAL AIR POLLUTION - Serrano Lomelin, Jesus (Paediatr Child Health, 2018)
BACKGROUND: The relationship of many hazardous pollutants present in ambient air with adverse birth outcomes (ABO) is still unknown, particularly from those released by industry. The knowledge gap is even greater when considering the impact of mixtures of hazardous pollutants on pregnancy outcomes. OBJECTIVES: We aimed to collaboratively overcome methodological limitations to identify potential hazardous mixtures of industrial air pollutants spatially related to the occurrence of ABO in Alberta. DESIGN/METHODS: We applied integrative data analyses on large existing databases (2006–2012) from (i) the National Pollutant Release Inventory on chemicals released into air by industry; (ii) the Alberta Perinatal Health Program on births, known maternal risk factors for ABO, and the maternal postal code at birth; (iii) an area-level socioeconomic status index (SES). We developed a novel spatial data mining (DM) algorithm to identify significant spatial colocation rules of combinations of emitted chemicals and ABO (i.e., preterm birth [PTB], small for gestational age [SGA], and low birth weight at term [LBWT]). We used a Geographic Information System (GIS) to assign exposures to residences within 10 km of emission sites. We used epidemiological analysis to calculate the corresponding odds ratios of exposures to chemical mixtures and the occurrence of ABO, adjusted by maternal covariates and SES. RESULTS: DM distinguished eleven rules combining three chemicals - gases, particulate matter and organics - as associated with ABO. GIS assigned exposure and epidemiological analysis identified seven rules with increased odds for induced PTB, SGA, and LBWT. One exclusively increased the odds for PTB (15%). CONCLUSION: The combined interdisciplinary use of data mining, GIS, and epidemiology strategies enabled us to identify the risks associated with mixtures of hazardous chemicals and ABO – findings that proved elusive when applying methodologies individually. These discoveries enhance our understanding of the role of chemical mixtures in ABO.